Distribuição da variabilidade genética em populações naturais de baccharis trimera (less) dc. (carqueja) no sul do Brasil. - Auler, Neiva Maria Frizon (2004)
Carqueja (Baccharis trimera) is a native plant from South America, occurs in several settings, it is highly employed in popular medicine, and has been explored under a grasping way. This study had the purpose of producing information for the establishment of adequate strategies to the conservation of genetic resources of this specie. Assuming this, one searched for information related to the reproductive and genetic aspects of this specie. In the cytogenetics analysis, one looked for information related to the number of chromosomes, formation of male gametes (microsporogenesis) and polinic viability within eight native populations in the states of Rio Grande do Sul and Santa Catarina. In the calculation of the number of chromosomes, an average of 10 metaphasics cells by population was analyzed. It was used Giemsa 2% (v/v) dye. In the microsporogenesis analysis, the chromosomes association and distribution stages in the meiosis, as well as the formation of tetrads and polinic viability by the test of (2 (P(0,01) were compared. The dye used in the cells identification was propionic carmin 2% (m/v) and for the estimate of pollen viability, three different dyes were tested: propionic carmin 2%, orcein acetic 2% (m/v) and alexander reaction. For the genetic variability classification, samples of ten natural populations of adults and four to maternal progenies, come from southern Brazil, were colected. Allozyme markers were used, revealed from the electrophoresis in starch gel (penetrose 30 at 13%), with Tris-citrate gel-electrode buffer for the ACP, a - EST, b - EST, MDH, PRX, NADHDH and GTDH enzimatic systems. For the genetic structure portrayal, F de Wright s statistics were used. The reproductive system was classified from the evaluation of the existence of panmixy and inbreeding equilibrium, as well as from the multiloci rate crossing estimate. The main results revealed that the populations analyzed are diploids with 2n=2X=18 chromosomes. Within the eight populations of Baccharis trimera, either in meiosis I and meiosis II, the percentage of normal cells, meiotic index and pollen viability was up to 85%. These data indicate that the populations have a normal microsporogenesis in the development process of the specie, having no problems in its introduction to selection, crossing and seed production programs. When comparing the three dyes, significant differences were observed among them, what suggests that alexander reaction may be the most reliable in order to estimate the pollen s viability in this specie. The results obtained from the allozyme markers revealed high levels of diversity either in adults (P=71% A=2,1, Ho=0,217 and He=0,215) and progenies (P=81%, A=2,4, Ho=0,272 e He=0,269). Mostly of the genetic variability of Baccharis trimera is inside the populations (FST = 0,0326), with a surplus of heterozygotes in most populations. There are indicators that the effective populational size and the vegetation type are the most influencial factors in the differences found among the populations. The specie is allogamic with Tm=1,05. The populations studied are under an equilibrium of panmixy and inbreeding. If taken together, the results of this research give referential that can define strategies for the conservation of genetic resources of this specie.